2020
DOI: 10.1016/j.dhjo.2019.100844
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to, and facilitators of, access to cancer services and experiences of cancer care for adults with a physical disability: A mixed methods systematic review

Abstract: BackgroundCancer services need to be inclusive and accessible by everybody, including people with disabilities. However, there is evidence suggesting that people with disabilities experience poorer access to cancer services, compared to people without disabilities. ObjectivesTo investigate the barriers and facilitators of access to cancer services for people with physical disabilities and their experiences of cancer care. MethodsA mixed-method systematic review was conducted following the Evidence for Policy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 71 publications
0
46
0
2
Order By: Relevance
“…In studies of other cancer screenings, health inequality in people with disability is common. A systematic retrospective study showed that the utilization rate of cancer screening in people with disability was significantly lower than that in people without disability [ 6 ], and some research on other cancers in Taiwan has also led to similar conclusions [ 10 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of other cancer screenings, health inequality in people with disability is common. A systematic retrospective study showed that the utilization rate of cancer screening in people with disability was significantly lower than that in people without disability [ 6 ], and some research on other cancers in Taiwan has also led to similar conclusions [ 10 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study using public data from the National Health Interview Survey also showed that people with disability were less likely to undergo CRC screening in 1998, but there was no difference in 2010 [ 5 ]. In contrast to the above viewpoints, one systematic review in 2020 screened more than 5000 articles and, after analysing 18 of them, concluded that although people with disability share many of the same barriers as people without disability, their utilization rate of cancer treatment is not higher than that of people without disability but their utilization rate of cancer screening is much lower [ 6 ]. In Taiwan, where free health checks have been available to adults for more than a decade, several studies have shown that people with disability are significantly less likely to receive free health checks than others [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Informational support from other people with disability can help patients identify accessible medical facilities for both preventive screening and treatment, as well as identify healthcare providers equipped to manage cancer care in the context of underlying disability. Previous studies highlighted physical access barriers to cancer treatment for people with disability, notably inaccessible medical equipment, 10–13 requiring that people with disability plan ahead in anticipation of such challenges to avoid delays in care. Arranging other forms of support (i.e., identifying caregivers who could provide physical assistance with ADLs over the course of treatment) is also critical, as cancer can exacerbate mobility impairments and reduce independence with ADLs 11 …”
Section: Discussionmentioning
confidence: 99%
“…They also experience cancer care disparities, notably lower likelihoods of receiving potentially life‐saving surgery 7 , 8 or other standard treatments 9 . Research interviews with people with disability have identified barriers to screening services and cancer care, including physical access barriers, 10‐13 inadequate preparedness among clinicians and facilities for accommodating disability, 12 , 13 and challenges navigating health promotion services for cancer survivors 14 …”
Section: Introductionmentioning
confidence: 99%
“…The confidence of the overarching synthesised findings derived from descriptive quantitative (that had undergone qualitisation) and qualitative research was assessed using the Confidence in the Evidence from Reviews of Qualitative research (CERQual) approach [ 56 ] and the findings from quantitative experimental research was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach [ 57 ]. The original CERQual approach was designed for qualitative findings but has previously been used by members of this research team (DE) in additionally adopting CERQual for the assessment of the confidence of synthesised findings from descriptive quantitative studies that have undergone qualitisation [ 58 – 60 ]. The confidence of synthesised review findings is based on the assessment of four components: the methodological limitations of the qualitative studies contributing to a synthesised review finding, the relevance to the review question of the studies contributing to a synthesised review finding, the coherence of a synthesised review finding, and the adequacy of data supporting a synthesised review finding.…”
Section: Methodsmentioning
confidence: 99%